2019
DOI: 10.5114/aoms.2019.87537
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the association between HOTAIR polymorphisms and susceptibility to breast cancer

Abstract: Introduction: Many studies are drawing attention to the associations of HO-TAIR polymorphisms and susceptibility to breast cancer, while the results remain inconsistent. We conducted a meta-analysis on the association of four common HOTAIR polymorphisms with breast cancer susceptibility. Material and methods: Eligible published articles were searched in PubMed, Embase, Cochrane library databases and Web of Science databases up to July 2019. Odds ratios with 95% confidence intervals were used to identify potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Contrary to our findings, it has been observed that there was a significant relationship between the rs920778 polymorphism and a high incidence of BC in women from Turkey [ 42 ], Iran [ 43 ], India [ 44 ], and China [ 30 , 45 ]. Based on a meta-analysis of 4 studies with 4936 cases and 5214 healthy controls investigating the association of four HOTAIR SNPs with BC vulnerability, it was found that rs920778 polymorphism significantly lowered the risk of BC under heterozygous, homozygous, and recessive models among the West Asians, and increased BC risk under dominant and allele models within the East Asian population [ 34 ]. Furthermore, some reports have indicated that HOTAIR SNP rs920778 exhibits variable results in the same population but in distinct cancer types such as gastric [ 46 ] and breast [ 42 ], which suggests that there are variations in the polymorphism throughout different malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrary to our findings, it has been observed that there was a significant relationship between the rs920778 polymorphism and a high incidence of BC in women from Turkey [ 42 ], Iran [ 43 ], India [ 44 ], and China [ 30 , 45 ]. Based on a meta-analysis of 4 studies with 4936 cases and 5214 healthy controls investigating the association of four HOTAIR SNPs with BC vulnerability, it was found that rs920778 polymorphism significantly lowered the risk of BC under heterozygous, homozygous, and recessive models among the West Asians, and increased BC risk under dominant and allele models within the East Asian population [ 34 ]. Furthermore, some reports have indicated that HOTAIR SNP rs920778 exhibits variable results in the same population but in distinct cancer types such as gastric [ 46 ] and breast [ 42 ], which suggests that there are variations in the polymorphism throughout different malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Several SNPs, located in the intronic region of the HOTAIR gene, have been reported to regulate its expression level [ 30 32 ]. These SNPs are expected to be related to the occurrence, progression, recurrence, and metastasis of BC and serve as a novel therapeutic target for the disease [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation